Prevalence of Primary Dysmenorrhoea and Its Impact on Academic Performance among Croatian Students during the COVID-19 Pandemic - Marta Horvat; Doroteja Pavan Jukić; Lovro Marinović; Dina Bursać; Rosana Ribić; Marijana Neuberg; Danijel Bursać (Obstetrics and Gynecology International)
Background. Dysmenorrhoea is one of the most common gynaecological problems. Therefore, it is important to investigate its impact during the COVID-19 pandemic which has a great impact on the lives of menstruating people all over the world. Aim. To determine the prevalence and impact of primary dysmenorrhoea on academic performance among students during the pandemic. Materials and Methods. This cross-sectional study was conducted in April 2021. All data were collected by an anonymous self-assessed web‐based questionnaire. Due to voluntary participation in the study, 1210 responses were received, but 956 were left for analysis after exclusion criteria were applied. Descriptive quantitative analysis was performed and Kendall rank correlation coefficient was used. Results. The prevalence of primary dysmenorrhoea was 90.1%. Menstrual pain was mild in 7.4% of cases, moderate in 28.8%, and severe in 63.8%. The study found that primary dysmenorrhoea has a great perceived impact on all included aspects of academic performance. Most affected were concentration in class in 810 (94.1%) and doing homework and learning in 809 (94.0%) female students. There is also a correlation between menstrual pain intensity and its impact on academic performance (p<0.001). Conclusions. Our study found that the prevalence of primary dysmenorrhoea among students at the University of Zagreb is high. Painful menstruation greatly impacts academic performance and therefore it is important to do more research on this topic.